IMPLEMENTASI STRATEGI PEMASARAN MELALUI WEBSITE DENGAN METODE SWOT SEBAGAI UPAYA PENINGKATAN PENJUALAN - Putri, Anisa Meliantika; Manafe, Leonard Adrie; Wahyudi, Agus (Fakultas Ekonomi Universitas Kadiri, 2023)
This research was conducted with the aim of knowing the increase in sales with a marketing strategy through the website at PT. Roda Hammerindo Jaya (RHJ). This research was investigated based on increasingly advanced internet technology at this time. The author in analyzing this study the approach used is a qualitative approach with descriptive analysis. To measure strengths, weaknesses, opportunities and threats, the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) is used. Data techniques collected by researchers through interviews, observation and documentation. The resulting research is the strength that RHJ has, namely competitive prices by offering a variety of products. There is a weakness that is often the occurrence of empty stock items. The opportunity that RHJ has of selling through the website is one way to reach consumers broadly and to increase sales volume. The threat that is currently being faced is many business competitors selling similar products. So that it can be illustrated that the online marketing strategy through the website carried out by RHJ has strengths and opportunities that can be used optimally in promoting products online.